EFFECT OF PLACEMENT TEST TO SPEED UP PAKET C LEARNING IN SKB KOTA BANDUNG - Cinta Darma (IKIP Siliwangi Bandung, 2021)
Equivalent education Paket C is an educational alternative that can be chosen by the community. Students who enter the Paket C program are not only those who have just graduated from SMP / MTs / SMPLB / Paket B, dropped out of high school or vocational school, but those who have graduated or dropped out of school years ago, so that sometimes their administrative requirements have been lost. However, they already have learning experiences based on their life experiences, these competencies must still be respected. The placement test is one way to place students according to their competencies. The purpose of this study was to determine the effect of the placement test on the learning acceleration of Paket C. The approach used in this study was a quantitative approach that measured the results of the effect of the placement test on the learning acceleration of students. Placement test with the completeness of the Paket C module. By conducting a placement test it can be seen how many modules have been completed and how many modules have not been completed. The completeness of this module shows that the competence in the module has been mastered by the test taker so that the test taker does not need to repeat learning in the module. So this placement test can place students, according to the abilities they already have. So it can be concluded that the Paket C equivalent placement test can accelerate the learning process of students.